Three-times-weekly, post-dialysis cefepime therapy in patients on maintenance hemodialysis: a retrospective study. Issue 1 (December 2016) - Descombes, Eric; Martins, Filipe; Hemett, Ould; Erard, Veronique; Chuard, Christian
Abstract Background In hemodialysis patients, post-dialysis treatment with intravenous antibiotics permits even severe infections to be managed on an outpatient basis. Cefepime is a fourth-generation cephalosporin with a broad spectrum of action in monotherapy. We report on the pharmacokinetics of cefepime in post-dialysis therapy. Methods Since June 2012, twelve infections were treated with post-dialysis cefepime in 9 patients on high-flux hemodialysis. The initial post-dialysis dose of cefepime was approximately 15 mg/kg. The following doses were adapted according to the trough serum levels obtained before the subsequent dialysis in order to be above the EUCAST breakpoints for susceptible organisms and above the MIC90. Residual plasma concentrations were determined before (n  = 30) and after (n  = 17) dialysis by liquid chromatography–mass spectrometry. Results Overall, the mean ± SD dose of cefepime was 920 ± 270 mg (14.5 ± 5.1 mg/kg), but it was significantly lower before the 48 h interval (775 ± 210 mg or 12.7 ± 4.5 mg/kg) compared to the 72 h interval (1125 ± 225 mg or 17.2 ± 4.9 mg/kg) (p  < 0.05). The mean trough pre-dialysis concentrations were 10.7 ± 3.9 mg/l and 11.3 ± 5.6 mg/l at 48 and 72 h, respectively. These levels always largely exceeded the EUCAST susceptibility breakpoints for all the targeted bacteria (>1 mg/l) with the exception of Pseudomonas aeruginosa (>8 mg/l). Cefepime concentrations were higher in anuric patients compared to those with preserved diuresis (15.6 ± 3.5 vs 9.25 ± 3.6 mg/l;p  < 0.001) and decreased on average by 81 % during dialysis (from 10.5 ± 3.7 to 1.96 ± 1.2 mg/l;p  < 0.001). The clinical outcome of all patients was good. Conclusions Outpatient treatment with cefepime administered post-dialysis three-times-weekly was effective and well-tolerated in our patients. According to our data, in patients infected by highly susceptible pathogens a fixed dose of cefepime of 1 g before every 48-h interval and of 1.5 g before every 72-h interval should be recommended, without need of routine monitoring of the cefepime blood levels. In patients having an infection with less susceptibles pathogens as P. aeruginosa, and particularly in those among them exhibiting residual renal function, higher initial doses are necessary (1.5 g before a 48-h interval and 2.0 g before a 72-h interval) with adaption according to the subsequent pre-dialysis trough serum levels.